Connective Tissue Graft as a Predictable Curtain for Aesthetics: A Case Report - Lamichhane, Simant; Humagain, Manoj; Dawadi, Asmita (Journal of Nobel Medical College, 2021)
Dental implant practice has now become a major choice for replacement of missing teeth in modern dentistry. Over the years, the success rate of dental implants has increased from 80-90% to 96-98%. However, due to lack of proper availability of soft tissue and hard tissue along with improper alignment of dental implants often pose aesthetic concerns in anterior aesthetic zone though the implant is fully osseointegrated with no signs of clinical mobility. This case report presents a case of a 21 years old male with a history of tooth loss due to trauma 8 months back and rehabilitation with dental implant 6 months back. On examination, mid-labial recession of around 3mm associated with #11 with no clinical signs of overlying inflammation was noted. Intact bone support was revealed by IOPAR. The recessed area around dental implant was managed with connective tissue graft and coronally advanced flap.